2022
DOI: 10.30631/psej.v2i2.1549
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Discovery Learning Berbantuan Macromedia Flash8 Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Ipa

Abstract: Penelitian ini bertujuan untuk meningkatkan hasil belajar IPA siswa menggunakan model discovery learning berbantu macromedia flash 8. Jenis penelitian yang digunakan adalah penelitian tindakan kelas (PTK) dengan subjek penelitian adalah siswa kelas VIII SMPN 17 Kabupaten Tebo dengan jumlah siswa 38. Data dikumpulkan dengan metode observasi, interview, dokumentasi dan angket. Data dianalisis secara deskriptif.  Hasil penelitian ini menunjukkan bahwa pembelajaran fisika menggunakan model discovery learning berba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In line with the research of Atika et al, 2018 through the discovery method in the learning process, video media functions as stimulation or data collecting and facilitates data processing activities. In line with Putri's (2022) research learning with the discovery learning model with the help of animated videos facilitates the stimulation stage and collects data that makes it easier for students to complete various levels of data processing activities (Putri et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the research of Atika et al, 2018 through the discovery method in the learning process, video media functions as stimulation or data collecting and facilitates data processing activities. In line with Putri's (2022) research learning with the discovery learning model with the help of animated videos facilitates the stimulation stage and collects data that makes it easier for students to complete various levels of data processing activities (Putri et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Similar research conducted by (Potu & Poluakan, 2020) showed that the discovery learning model assisted by interactive multimedia can improve students' critical thinking skills. Likewise, the results of research from Putri et al (2022) show that the discovery learning model assisted by animated videos can improve the learning outcomes of VII grade junior high school students on digestive system material. Based on the description of the background of the problem above, and considering that no research shows the effect of the Discovery Learning model assisted by animated video on the critical thinking skills of class XI high school students on the material of the digestive system, the researcher is interested in conducting a study entitled "The Effect of Discovery Learning model assisted by Animated Video on Critical Thinking Skills of Class XI Students on Digestive System Material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation